Pion radiative weak decays in nonlocal chiral quark models - Gómez Dumm, Daniel Alberto (2011)
We analyze the radiative pion decay π⁺ → e⁺ νeγ within nonlocal chiral quark models that include wave function renormalization. In this framework we calculate the vector and axial-vector form factors F V and F A at q² = 0 — where q² is the e⁺ ν e squared invariant mass — and the slope a of F V (q²) at q² → 0 . The calculations are carried out considering different nonlocal form factors, in particular those taken from lattice QCD evaluations, showing a reasonable agreement with the corresponding experimental data. The comparison of our results with those obtained in the (local) NJL model and the relation of F V and a with the form factor in π⁰ → γ ⁎ γ decays are discussed.